Seven requests/ Amira Budi Mutiara; penyunting, Hutami Suryaningtyas; ilustrasi, Gloria Grace Tanama - AMIRA BUDI MUTIARA, 1995-; Hutami Suryaningtyas; Gloria Grace Tanama (Bentang belia, 2012)
vi, 174 hlm. : ilus. ; 19 cm